Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

1 = -1

  1. Jun 17, 2005 #1
    This is my first post HI everyone!!!!

    Whats wrong with this.

    1 = sqrt(1) = sqrt (-1*-1) = sqrt(-1)*sqrt(-1) = i * i = i^2 = -1


    1 = -1

    0= -2,2

    0 = Real Number Set


    Dammit im right! And everyone in the history of maths is wrong!


  2. jcsd
  3. Jun 17, 2005 #2
    Holy ****! You've gotten us! :rolleyes:

    You're mistake is in the second step, you need to consider the full definition, parameter-usage and application of the square root function before splitting it up like that.
  4. Jun 17, 2005 #3


    User Avatar
    Science Advisor
    Homework Helper

    Simply put:Sqrt always returns a real positive value.

    [tex] \sqrt{ab}=\sqrt{|a|}\sqrt{|b|} [/tex] , [tex]ab\geq0[/tex].

  5. Jun 17, 2005 #4


    User Avatar
    Science Advisor
    Homework Helper

    [itex]\sqrt{-1 \cdot -1}\not=\sqrt{-1}\cdot \sqrt{-1}[/itex].
  6. Jun 17, 2005 #5


    User Avatar
    Science Advisor
    Homework Helper

    Same thing but a bit more obvious, your step is like saying:

    [tex]|1| = |-1|[/tex]


    [tex]1 = -1[/tex]
  7. Jun 17, 2005 #6


    User Avatar
    Science Advisor

    What everyone else has said is true. And it is basically due to the fact that the complex numbers cannot be ordered. If we define i by "[tex]i= \sqrt{-1}[/tex] or even i2= -1, we cannot distinguish between "i" and "-i". (Since the complex numbers are not ordered, we can't say "the positive root" and "the negative root".)

    More precise is to define the complex numbers as pairs of real numbers (a, b) and define addition by (a,b)+ (c,d)= (a+c, b+d) and multiplication by (a,b)(c,d)= (ac-bd, ad+ bc). (Then a+ bi is just a notation for (a,b).) Using that notation this problem disappears.
  8. Jul 13, 2005 #7
    (ab)^1/2 = a^1/2*b^1/2 if and only if ATLEAST one of a, b is Non negative. If a and b are both non negative then (ab)^1/2 = - (a)^1/2*(b)1/2 ;) cheers!!
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook